PENGARUH FAKTOR EKONOMI MAKRO TERHADAP HARGA EMAS DI INDONESIA - Wisnu Yuwono; Calvin Calvin; Johny Budiman; Dewi Khornida Marheni (JURNAL LENTERA BISNIS, 2025)
This study was conducted with the aim of analyzing the impact of macroeconomic variables on gold prices in Indonesia. The variables analyzed include inflation, interest rates, Gross Domestic Product (GDP), and unemployment rates. The data used covers an eleven-year period, from January 2013 to December 2023. The results of the study show that inflation and interest rates have a negative but insignificant effect on gold prices. Conversely, GDP and unemployment rates have a significant positive effect on changes in gold prices in Indonesia. The results of this study can be a reference for investors in planning gold investments in the future.